Physicochemical, nutritional, and bioactive properties of pulp and peel from 15 kiwifruit cultivars. (August 2021) - Liang, Jingjing; Ren, Yaopeng; Wang, Yu; Han, Mengzhen; Yue, Tianli; Wang, Zhouli; Gao, Zhenpeng
Abstract: Kiwifruit, as a source of vitamin C and phenolic profiles, is well known for its nutrition and health benefits. To select varieties suitable for deep processing and better utilise kiwifruit by-products, a comprehensive characterisation of 15 kiwifruit cultivars was performed. The characterisation included physicochemical and nutritional properties, as well as the phenolic compounds of each pulp and peel. The results revealed that kiwifruit exhibited differences in quality by variety, 'Hongyang' and 'Yate' may be more suitable for fresh consumption due to their high sugar-to-acid ratio (10.39 and 10.27, respectively). All cultivars contained fructose (13.06–33.77 mg/g) and glucose (13.67–36.6 mg/g) as the dominant sugars. Also, kiwifruits had high vitamin C content (47.24–171.64 mg/100 g) and total phenolics (75.43–316.14 mg GAE/100 g FW). Quinic acid (4.78–19.85 mg/g) and citric acid (4.22–11.36 mg/g) were the main organic acids. Most kiwifruit peel samples contained higher amounts of phenolic compounds, especially gallic acid, p -hydroxybenzoic acid, epicatechin, and catechin, than did pulp. A hierarchical cluster analysis revealed that the 'Miliang', 'Allison', 'Kuimi', 'Jinkui', and 'Jinxiang' cultivars have potential for the development of high value-added antioxidant polyphenol products. Graphical abstract: Image 1 Highlights: Cultivar was the main factor effecting the quality of kiwifruit. Kiwifruit peel contained higher amounts of phenolic compounds than did pulp. Physicochemical and nutritional properties were compared. The result obtained will provide a reference for fruit deep processing.